Agronomy, breeding and cytogenetic factors affecting growth of Stevia rebaudiana Bertoni - Abdullateef, Raji Akintunde (Kulliyyah of Science, International Islamic University Malaysia, 2013)
Stevia rebaudiana bertoni is known for its production of sweet glycosides, an alternative to sugar due to its zero calorie and strong health and dietary implications. The cultivation of stevia in this country is hampered by few factors. First, stevia produces flowers at early stage under Malaysia photoperiod condition, thus leading to poor leaf development where the leaves are the most needed for sweetener extraction. In addition, stevia accessions do not grow well under local condition, and there has been no breeding work to develop suitable cultivars. Moreover, no suitable vegetative propagation techniques have been established, leading to high production cost. Also seed germination is very low making production of plant materials difficult and expensive. Lastly, among the sweet glycosides, rebaudioside A is more preferred, but the content is low compared to stevioside in natural varieties. Thus, the project was undertaken to study the agronomy, breeding and cytogenetic factors affecting growth of Stevia rebaudiana Bertoni under Malaysian condition. Firstly, agronomic studies were conducted on the effects of stem cutting types, position and IBA on rooting. YAS-MS012 cuttings treated with IBA concentration of 2.3 mM performed best. Under light treatment condition, YAS-MS012 treated with red light showed highest rooting quality and IBA treatment may not be necessary. Pollen viability test using cotton blue-in-lactophenol and germinability test using boric acid in collected accessions showed high pollen viability range from 87 to 93 %. The pollen germinability ranged from 62 to 74 %. Boric acid concentration of 0.25 mg/ml was optimal. Seed viability using 1% tetrazolium chloride was found to be 68.67 %; whereas germinability using red and white lights was found to be 41 and 31 % respectively. New technique improved seed germination to 67.33 %, than the initial technique, which germinated a maximum of 41 % seeds. ANOVA showed there are significant differences between treatments at p < 0.05. Utilization of Trigona was highly effective in increasing the total number of seed production, specifically on black seeds. Day light extension using white, yellow, and red lights delayed flowering period and promoted vegetative yield in S. rebaudiana in comparison to control. Red light had the highest influence (p < 0.05). Pruning increased plant height, number of branches and number of leaves in S. rebaudiana (p < 0.05). The collected accessions were found to be genetically divergent where homogeneity test (p < 0.05) clustered them into four groups. Breeding was also carried out to develop stevia hybrids. Mutation using gamma irradiation showed that the LD50 was 55 grays. The number of germinated seeds was different in respect of doses. Genetic studies showed four types of chlorophyll mutants were induced. They are albina, chlorina, xantha and xantha-viridis. Frequency and spectrum analysis revealed chlorina has the highest occurrence of 33.03%. Tetraploidy induction using colchicine concentrations of 0.2 to 0.5 mM was performed. The concentration of 0.2% (w/v) was optimal in raising new tetraploids. However, HPLC analysis showed a reduced rebA and stevioside content in tetraploids, as compared to the diploid. Trigona increased cross-pollination between tetraploids and diploids. New triploid, RAAMBO/02, was developed. This research led to classical novelties, such as plant materials: (i) Tetraploid RAAMBO/01, (ii) Triploid RAAMBO/02, (iii) M1 RAAMBO/03, and (iv) M2 RAAMBO/04. Several prototypes were also developed (i) red light box for rhizogenesis, (ii) M2 seed dome for seed germination, and (iii) Trigona breeding net house for agronomy and breeding research. The current research also improved several experimental protocols: (i) rhizogenesis in stem cuttings, (ii) seed germination, and (iii) cytogenetic in stevia.